Application of ventriculoscopy in granulomatous amoebic encephalitis: a case report in China and literature review - Zheng, Zequan; Chen, Fajun; Qin, Lulu; Lu, Aili; Xu, Haoyou; Zhao, Min; Zhao, Yuanqi (Frontiers in Medicine, 2024)
Balamuthia mandrillaris is a kind of brain-eating amoeba leading to granulomatous amoebic encephalitis (GAE) with high mortality rate and limited effective treatment options. Its underlying pathological mechanisms are still poorly understood. Here we presented a 58-years-old man with Balamuthia mandrillaris meningoencephalitis, who died 33 days after onset. In this unique case, we introduced the use of ventriculoscopy in the treatment of B. mandrillaris meningoencephalitis. Through ventriculoscopy, we observed that the inflammatory response triggered by the disease was diffuse and extensive throughout the ventricles and meninges, not limited to the region of parasite invasion. Furthermore, under the precise guidance of ventriculoscopy, we implemented drug lavage therapy and intraventricular drainage, which, to a certain extent, managed to mitigate the progression of hydrocephalus and intracranial hypertension. Despite the unfortunate outcome of the patient's death due to brainstem hemorrhage, we reiterate the crucial role that surgical intervention plays in both diagnosing and managing amoebic encephalitis. This underscores the need for continued research and innovation in surgical techniques to enhance patient outcomes and combat this challenging neurological condition.